Inkonsistensi Putusan Mahkamah Konstitusi Terkait Kewenangan Mengadili Sengketa Pemilihan Kepala Daerah (Studi Kasus Putusan MK Nomor 072-073/PUU-II/2004 dan Nomor 97/PUU.XI/2013) - Setiawan, Sigit; , Iswanto, S.H., M.H; , Dr. Nuria Siswi Enggarani, S.H., M.H (2016)
Judicial review on the constitutionality of law is basically toughts as the check and balances mechanism by the Constitutional Court as the guardian of Constitution. Constitutional Court"s Verdict was dispose in final an binding - gives so much correction to the inconstitutional law, which not necessary with consitution content or even the nation"s whises in our constitution. As the guardian of constitution, Constitutional Court should give guarantee of rule of law nation could stand for erectly. What exactly happened is, some of Constitutional Court"s Verdicts is seems full of controversy. Inconsistency Constitutional Court"s Verdict can be seen when it run judicial review on the constitutionality of law in dispute of local government election context, it cannot be separated from the Constitutional Court"s competence which has an authority to sit in on judgement of national election dispute, it viewed as the same as dispute of local government election, it is one of the Constitutional Court"s competence. This special intitution was made for constitutional case resolution, in one of verdict of judicial review number 072-073/PUU-II/2004 suggested that Constitutional Court have competence to sit in on judgement of dispute of local government election, but in verdict of number 97/PUU.XI/2013 declared for unjudge that case no more. Nemo judex in causa cua principle says that the judge cannot try to judge a case which it have a connection with him/herself. But, as a guardian of constituition, it has to stands for legal security to bring rule of law principle erectly. Keywords : Inconsistentcy, Constitutional Court"s Verdict, Dispute of local government election